THE LODRAN PRIMITIVE ACHONDRITE: PETROGENETIC INSIGHTS FROM ELECTRON AND ION MICROPROBE ANALYSIS OF OLIVINE AND ORTHOPYROXENE - Papike J.J.; Spilde M.N.; Fowler G.W.; Layne G.D.; Shearer C.K. (My University, 1995)
The Lodran primitive achondrite is thought to represent some of the earliest events in the differentiation of chondritic asteroids. Most researchers who studied Lodran believe that it is a restite from which a melt, enriched in the incompatible trace and minor elements, was extracted. This process is reflected by a lack of feldspar in the Lodran mineral assemblage. Presumably, after or during melting, a reduction event took place resulting in an increase in Mg/Fe near the rims of both olivine and orthopyroxene. The reduction process is far more advanced in olivine than in pyroxene because of the more rapid Fe#Mg diffusion rates in olivine. Narrow reaction rims (<10 μm) around orthopyroxene grains show a depletion in Ca, Al, Cr, Ti, REEs, and Y and an increase in Mg (reverse zoning). These systematics are largely the result of melting and to a lesser extent of reduction. Significant reaction of olivine has taken place by reduction and/or sulfidatuon and to a lesser extent by melting. This is reflected by a decrease in Fe, Co, and Ni and an increase in Mg towards the rims of olivine. The reactions by which reduction and/or sulfidation of olivine took place are not confirmed. However, the following represent two possible reactions: